(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The methodology for assessing the quality of public service at catering firms should be based on a comparison of consumer expectations and perceptions in relation to the service process, that is, the quality coefficient is determined as the difference between perception and expectations. In this case, the quality factor can be determined both by the indicator of interest and by the enterprise as a whole. Consequently, the criteria for assessing the quality of public service at catering establishments must be formed taking into account its type and class. To obtain primary information from consumers, it is necessary to organize and conduct a sociological study. When choosing a method of sociological research, it is advisable to give preference to interviews, since this is a rather flexible method of collecting information, based on direct contact between the interviewer and the respondent. The main advantage of the interview, in comparison with the questionnaire, is the ability to control the perception and understanding of the questions by the respondent; if necessary, the interviewer can explain the questions asked, and also clarify the respondent’s point of view with the help of additional questions.When conducting a sociological research by the interview method, the requirements for the formation of a questionnaire are significantly reduced. The list of questions asked to respondents should be expanded with personal questions, the purpose of which is to reflect: age, social status, average monthly income. These questions are necessary to represent the target group of consumers of public catering services.